2020
DOI: 10.35137/jmbk.v8i1.390
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kualitas Layanan Dan Suasana Toko Terhadap Kepuasan Pelanggan Toko Toys City Mall Sumarecon, Bekasi

Abstract: <em>This study aims to determine the effect of service quality and store atmosphere on customer satisfaction at Toys City Mall Summarecon Bekasi. This research is a quantitative research and survey research. The population of this study is the customer-owner owner of children's toys buyers Toy City Mall Mall Summarecon Bekasi. The number of samples is 60 respondents, while the sampling technique uses the saturated sample technique. The data of this research are primary data sourced from questionnaires th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…In previous research conducted by Thaib et al (2020) on the effect of service quality and store atmosphere on Consumer Satisfaction at the Toys City Mall Sumarecon Bekasi store concluded that store atmosphere supports increasing Consumer Satisfaction at the Toys City Mall Sumarecon Bekasi store. Furthermore, research conducted by Ndengane et al (2021) which examines the effect of store atmosphere on Consumer Satisfaction in Cape Town, South Africa.…”
Section: Store Atmosphere and Consumer Satisfactionmentioning
confidence: 96%
“…In previous research conducted by Thaib et al (2020) on the effect of service quality and store atmosphere on Consumer Satisfaction at the Toys City Mall Sumarecon Bekasi store concluded that store atmosphere supports increasing Consumer Satisfaction at the Toys City Mall Sumarecon Bekasi store. Furthermore, research conducted by Ndengane et al (2021) which examines the effect of store atmosphere on Consumer Satisfaction in Cape Town, South Africa.…”
Section: Store Atmosphere and Consumer Satisfactionmentioning
confidence: 96%
“…Untuk mengetahui teori hubungan dengan berbagai faktor yang akan diidentifikasi dalam pengaruh variabel X1 dan X2 terhadap keputusan pembelian untuk membeli produk pada April Eyewear. Berikut kerangka konseptual: Gambar 2 Kerangka Konseptual Sumber penelitian terdahulu: X1: Santoso (2022), Surti (2020), Thaib (2020), Soleha (2022) X2: Sabillah (2022), Purba (2020), Somantri ( 2022)…”
Section: Kerangka Konseptualunclassified
“…Faktor penentu dari kualitas pelayanan antara lain: Tangible, Empathy, Responsiveness, Reliability, dan Assurance. Hasil penelitian ini sesuai dengan penelitian sebelumnya yang telah dilakukan oleh Santoso (2022), Surti (2020), Thaib (2020), dan Soleha (2022) yang menyatakan bahwa kualitas pelayanan berpengaruh signifikan terhadap keputusan pembelian.…”
Section: Pembahasan Dan Analisis Dataunclassified